Kahoot!: Bring the Fun Into the Classroom! - Sabandar, Grace Nathania Clara; Supit, Noldy Richard; Suryana, Effendy (Universitas Sebelas Maret, 2018)
During the height of 21st Century Learning, educators across the globe are demanded to find ways, methods and techniques to engage modern learners in the learning process. Nowadays, with the simplicity provided by the Internet, it is not as difficult and painful to help with the process. One of the fun ways to educate learners is with games, digital games. Games are usually intended to increase learners’ desire for competition, goal achievement and genuine self-expression, all in the while games are also great to promote interactivity, have a set of rules with a quantifiable result, can be colorful, as well as appealing and extremely realistic. This paper is based on an interactive workshop which was focused in exploring the app, Kahoot!, that claims to provide educators with a chance to create a game-based assessment in different forms, such as multiple-choice questions, jumbled vocabulary, jumbled sentences. Healthy competition and rewarding good ideas provided by Kahoot! app also said to be motivational both to educators and for modern learners. It is expected that through this workshop participants are comfortable and able to incorporate Kahoot! into a variety of learning environments and will have the opportunity to design game-based learning events that can be used in the classroom. Finally, the workshop provided an opportunity for participants to discuss strengths, weaknesses, benefits and challenges in using Kahoot!.